Tom the naughty tooth fairy - Dale, Elizabeth (Great Britain Franklin Watts, 2018)
Tom is a Tooth Fairy in trouble! He's spent so much time playing he has forgotten to collect teeth and the Fairy Boss is not happy ... does Tom have time to go back?